Gender-Based Differences in the Influence of Authenticity and Memorable Experiences on Tourist Loyalty - Kusnayain, Yesiana Ihda; Hussein, Ananda Sabil; Wu, Hung-Che (Jurnal Aplikasi Manajemen, 2025)
The Indonesian archipelago boasts a distinctive and multifaceted cultural heritage. This study seeks to understand how memorable experiences and authenticity influence tourist loyalty in Indonesian urban heritage tourism. By examining these factors and the mediating role of satisfaction, we aim to contribute to the growth of Indonesia's tourism industry, which, while internationally recognized, still lags behind neighboring countries. Additionally, this study will explore gender differences in these relationships to provide a more nuanced understanding of tourist behavior. Using a structural equation modeling (SEM) approach, this study analyzes data from 350 respondents, who were tourists who visited the urban heritage in Indonesia. This study used cross-sectional data with a purposive sampling technique. The findings reveal that both memorable tourism experiences and authenticity exert a significant influence on tourist loyalty. Interestingly, the findings on gender differences indicate that gender does not significantly influence the relationship between memorable tourism experiences and tourist loyalty. Theoretically, this study enriches the literature on tourist loyalty and gender differences with a comprehensive construct. Finally, this study will be valuable for boosting tourist sustainability by considering a gender perspective, which helps stakeholders with the strategic implementation and policy.